An annotated checklist with a key to the genera of Australian psyllids (Hemiptera: Sternorrhyncha: Psylloidea) - Martoni, Francesco; Bartlett, Justin S.; Moir, Melinda L.; Steinbauer, Martin J.; Taylor, Gary S. (Zootaxa, 2024)
The diversity of the psyllids of Australia reflects that of the plants of this country, with large radiations and ecological dominance of Myrtaceae (e.g., Eucalyptus), Fabaceae (e.g., Acacia), Casuarinaceae (e.g., Allocasuarina, Casuarina) and Scrophulariaceae (e.g., Eremophila, Myoporum). Within Australian ecosystems, psyllids are critical components of food webs, especially with respect to providing energy-rich resources for many species of birds and insects and, historically, humans. Furthermore, in horticulture, agriculture and forestry, some Australian psyllid species are considered pests, causing leaf senescence and ‘dieback’, leaf deformation and inducing growth of sooty mould, with some adventive species capable of acting as vectors of plant pathogens. Several species are considered beneficial, having been introduced as biological control agents of weeds. Additionally, some Australian psyllids have established in other countries, or in regions within Australia that are not within their natural range; while others have such limited geographical ranges that they are of conservation concern. Here we provide an updated checklist of the species of Psylloidea present in Australia and updated a previous key to their genera based on adult morphology. This is the first checklist of the Australian psyllids compiled since the most recent global taxonomic classification, and provides detailed information on biogeographical, ecological and anthropogenic aspects, including global distribution, host plant data, pest status, conservation status, parasitoids, predators, and biological control programs. Our checklist includes information on 66 genera and 450 species, 414 formally described and 36 awaiting descriptions. This represents an increase of almost 20% of species since the last published checklist of 2004, which reported 354 described and 21 undescribed taxa. Additionally, we summarise the available information on more than 150 undescribed taxa. Finally, we reported here more than 60 new records, between distributions and host plant associations.